2012
DOI: 10.3346/jkms.2012.27.8.901
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of Chronic Obstructive Pulmonary Disease in Koreans: A Population-Based Study

Abstract: Chronic obstructive pulmonary disease (COPD) includes pulmonary components with increased comorbidity rates, as well as being a systemic disease. Comorbidities may frequently occur in COPD patients over 40 yr old. We report the comorbidities of patients with COPD, diagnosed by spirometry, in a population-based epidemiologic survey in Korea. Data were derived from the fourth Korean Health and Nutrition Examination Survey in 2008, a stratified multistage clustered probability design survey of a sample representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 19 publications
2
40
0
Order By: Relevance
“…This new knowledge emphasises the need to both consider COPD when managing other diseases and address other diseases when managing people with COPD. Our findings are consistent with previous population-based studies demonstrating an association between COPD and a wide range of comorbidities [13,[21][22][23][24][25][26][27][28][29]. For example, GARCIA-RODRIGUEZ et al [23] found an increased risk of lung cancer (relative risk 3.33, 95% CI 2.33-4.75) and heart failure (relative risk 2.94, 95% CI 2.46-3.51), while NG et al [27] found an increased risk of depressive symptoms (OR 1.86, 95% CI 1.25-2.75) among those with COPD compared with those without.…”
Section: Discussionsupporting
confidence: 83%
“…This new knowledge emphasises the need to both consider COPD when managing other diseases and address other diseases when managing people with COPD. Our findings are consistent with previous population-based studies demonstrating an association between COPD and a wide range of comorbidities [13,[21][22][23][24][25][26][27][28][29]. For example, GARCIA-RODRIGUEZ et al [23] found an increased risk of lung cancer (relative risk 3.33, 95% CI 2.33-4.75) and heart failure (relative risk 2.94, 95% CI 2.46-3.51), while NG et al [27] found an increased risk of depressive symptoms (OR 1.86, 95% CI 1.25-2.75) among those with COPD compared with those without.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are in line with the findings from the Women's Health Study, in which Song and colleagues found that women who had ever reported COPD had an increased risk of co-morbidity of type 2 diabetes; the multivariate relative risk was 1.38 [16]. In contrast, studies by Joo and colleagues of a Korean population [21] and by Lindberg et al of a Swedish population [20] found no association between COPD and type 2 diabetes. In the latter study restrictive lung function was strongly associated with diabetes compared with both normal and obstructive lung function.…”
Section: Discussionsupporting
confidence: 92%
“…Second, we defined comorbidities objectively using laboratory results, such as fasting glucose and HbA1c for DM, and physical findings, such as systolic and diastolic blood pressure, for hypertension. In most previous studies, the definition of comorbid conditions of COPD depended on self-reported questionnaires [8,31,32].…”
Section: Discussionmentioning
confidence: 99%